Characteristics of Thin-layer Infrared Drying of Green Bean - Doymaz, Ibrahim; Kipcak, Azmi Seyhun; Piskin, Sabriye (CZECH ACADEMY AGRICULTURAL SCIENCES, 2015)
The effect of infrared (IR) power on drying kinetics, rehydration, and colour of green beans was investigated. The drying experiments were carried out at 83, 104, 125, 146, 167, and 188 W. It is observed that drying characteristics, rehydration, and colour of bean slices were greatly influenced by infrared power. The drying data were fitted with five thin-layer drying models available in the literature. Results showed that Midilli et al. and Aghbashlo et al. models are superior to the other models for explaining the drying kinetics of green bean slices. Effective moisture diffusivity was calculated in the range of 6.57 x 10(-10) to 4.49 x 10(-9) m(2)/s. Activation energy was estimated by a modified Arrhenius type equation and found to be 11.379 kW/kg.
Keywords: effective diffusivity; activation energy; infrared power; mathematical modelling; MOISTURE DIFFUSIVITY; ONION SLICES; ROUGH RICE; KINETICS; RADIATION; TEMPERATURE; QUALITY; CARROT; MODEL; BED; Food Science & Technology